Genetic diversity and morphological responses of Capsicum annuum varieties under aluminum stress - ANDRIYANI ANDRIYANI; Nurul Jadid (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Andriyani, Jadid N. 2021. Genetic diversity and morphological responses of Capsicum annuum varieties under aluminum stress. Biodiversitas 22: 2576-2582. Capsicum annuum is one of the most cultivated vegetable crops in the world. Its fruit contains various beneficial metabolites which possess antioxidant activities. Fertilizers play important role to increase plant productivity. However, excessive use of fertilizers could harm the environment. Heavy metals, including aluminum (Al), contamination have been reported to negatively affect plant production and inhibit root growth. C. annuum var Ciko, Lingga, Lembang1, and Tanjung2 are commonly cultivated in Indonesia. However, the genetic diversity of those plants and their responses to Al stress condition are still unknown. Therefore, our study aimed to analyze the genetic diversity of four C. annuum cultivars and to observe their morphological responses under Al stress conditions. The genetic diversity was analyzed using five universal inter-simple sequence repeat (ISSR) primers. Our results showed that the PIC values ranged from 0 (primer 825) to 0.6375 (Primer 9). The UPGMA phylogenetic construction also demonstrated that the cv. Lembang1 is closely related to the cv Lingga. Meanwhile, cv Tanjung 2 is closely related to the cv. Ciko. Each cultivar also performed different morphological responses under Al stress conditions. Our data showed that Al affected significantly root growth but not affected their plant height. Aluminum at 100 ppm significantly decreased root length of cv. Lingga